Combined Effect of Start of Direct Injection Timing and Fuel Temperature on Combustion and Pollutant Emissions of a Reactivity Controlled Compression Ignition Operated Single-Cylinder Diesel Engine - Altun, Sehmus; Firat, Mujdat; Okcu, Mutlu; Varol, Yasin (Sae Int, 2023)
Reactivity controlled compression ignition (RCCI) engines still suffer from high levels of carbon monoxide (CO) and unburned hydrocarbon (uHC) emissions at light loads, which is one of the main challenges to be overcome before its implementation in practical engines. The injection strategies and charge temperature are two important factors that affect the mixture stratification and fuel reactivity, which have a great impact on the formation of pollutants in RCCI engines. Therefore, it is of great importance to study the effect of these variables in order to support the development of RCCI engines. In this study, an experimental investigation was carried out to study the combined effect of the start of direct injection (SOI) timing and fuel temperature on RCCI combustion char-acteristics in a single-cylinder research engine equipped with a common rail under constant engine speed and energy delivery ratio. In the experimental research, EN590 petroleum diesel was used as the high-reactivity fuel (HRF) while iso-octane was employed as the low-reactivity fuel (LRF) that is sprayed into the intake to be mixed with air before diesel injection. The SOI timing was changed from 15 degrees crank angle (degrees CA) to 27 degrees CA before top dead center (bTDC) with 3 degrees CA increments while both LRF and HRF temperatures were also studied at 343 K and 278 K. The results indicated that the increase in fuel temperature improved the RCCI combustion performance regardless of SOI timing change. Under these conditions, about 11% and 25% reductions in HC and CO emissions were recorded, respectively, while a notable improvement is observed in the indicated mean effective pressure (IMEP). Moreover, it was observed that by advancing the SOI timing to 27 degrees CA bTDC, a reduction in combustion duration (CD) and increase in combustion temperature and rate of pressure rise (RoPR), together with reductions in CO, unburned HC, and smoke emissions at the expense of high NOx emissions, could also be obtained. These changes were observed to be more pronounced in the case where the HRF was heated to 343 K than in the other cases.
Keywords: RCCI combustion Start of; injection (SOI) timing Fuel; temperature Exhaust; emissions